Polyaniline/β-MnO2 nanocomposites as cathode electrocatalyst for oxygen reduction reaction in microbial fuel cells. (May 2018) - Zhou, Xinxing; Xu, Yunzhi; Mei, Xiaojie; Du, Ningjie; Jv, Rongmao; Hu, Zhaoxia; Chen, Shouwen
Abstract: An efficient and inexpensive catalyst for oxygen reduction reaction (ORR), polyaniline (PANI) and β-MnO2 nanocomposites (PANI/β-MnO2 ), was developed for air-cathode microbial fuel cells (MFCs). The PANI/β-MnO2, β-MnO2, PANI and β-MnO2 mixture modified graphite felt electrodes were fabricated as air-cathodes in double-chambered MFCs and their cell performances were compared. At a dosage of 6 mg cm −2, the maximum power densities of MFCs with PANI/β-MnO2, β-MnO2, PANI and β-MnO2 mixture cathodes reached 248, 183 and 204 mW m −2, respectively, while the cathode resistances were 38.4, 45.5 and 42.3 Ω, respectively, according to impedance analysis. Weak interaction existed between the rod-like β-MnO2 and surficial growth granular PANI, this together with the larger specific surface area and PANI electric conducting nature enhanced the electrochemical activity for ORR and improved the power generation. The PANI/β-MnO2 nanocomposites are a promising cathode catalyst for practical application of MFCs. Highlights: The PANI/β-MnO2 nanocomposites are synthesized successfully. The nanocomposites serve as electrocatalysts for the air cathode of MFCs. The performance of PANI/β-MnO2 nanocomposites modified MFC is enhanced. The nanocomposites are potential electrocatalysts for air-cathode MFCs.